Primary Hyperaldosteronism in Clinical Practice - Gulrukh Alimoukhamedova; Zamira Khalimova (Scholars Digest Publishing, 2023)
The data obtained in the study of the clinical features of aldosterone-producing adrenal adenomas indicate that aldosteromas are more common in young working age (the average age of patients was 42.4 ± 12.4 years old, and the peak incidence was at the age of 18 to 44 years old) with a predominance among females. The classical clinical triad, which includes a combination of three main syndromes (AH, neuromuscular and renal), was found only in 62.5% of the patients. The leading clinical manifestation in all the patients with aldosteroma in 100% of the cases was hypertension, which was permanent in 75% of the patients, mixed in 12.5%, while constant malignant hypertension was observed in 12.5% of the cases. At the same time, stage 1 (50%) and stage 2 hypertension (37.5%) were registered most often in patients with aldosterone-producing adenomas, and only stage 3 hypertension was registered in 12.5%. It should be noted that the combination of hypertension, especially in young people, and a burdened family history of hypertension and its complications among the relatives of the first line kinship should serve the basis for excluding aldosterone-producing adrenal adenomas.
Keywords: adrenal tumors, arterial hypertension, primary aldosteronism.